2011
DOI: 10.1128/iai.05456-11
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Deubiquitinase Inhibitor Increases Localization of Inducible Nitric Oxide Synthase to the Macrophage Phagosome and Enhances Bacterial Killing

Abstract: Macrophages are key mediators of antimicrobial defense and innate immunity. Innate intracellular defense mechanisms can be rapidly regulated at the posttranslational level by the coordinated addition and removal of ubiquitin by ubiquitin ligases and deubiquitinases (DUBs). While ubiquitin ligases have been extensively studied, the contribution of DUBs to macrophage innate immune function is incompletely defined. We therefore employed a small molecule DUB inhibitor, WP1130, to probe the role of DUBs in the macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…We chose to only pre-treat cells with compound before performing the infection in order to minimize any direct effect of the compounds on the bacteria. Moreover, based on our previous observations with the parent compound, the anti-infective effect of WP1130 occurs at an early stage of infection [29]. Among the 28 compounds used, only 5 derivatives caused a significant decrease in Listeria intracellular viability, and were selected for further analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to only pre-treat cells with compound before performing the infection in order to minimize any direct effect of the compounds on the bacteria. Moreover, based on our previous observations with the parent compound, the anti-infective effect of WP1130 occurs at an early stage of infection [29]. Among the 28 compounds used, only 5 derivatives caused a significant decrease in Listeria intracellular viability, and were selected for further analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We showed previously that WP1130 had no effect on Listeria growth in broth culture in the absence of host cells, suggesting that the decrease in intracellular bacterial viability was a consequence of WP1130 on target cells [29]. To determine whether the new WP1130-derivatives acted similarly, we tested the four best WP1130 derivatives for their effect on Listeria growth in axenic culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination regulates membrane protein sorting [29]; thus one could envision a role for NKLAM in regulating the trafficking of proteins related to bactericidal functions. In support of this concept, recent studies have demonstrated that inhibition of cellular deubiquitinases increased the trafficking of iNOS to phagosomes and significantly augmented macrophage L. monocytogenes killing [6]. Recent studies have also suggested that the ubiquitination machinery normally associated with autophagy is involved in recognizing and degrading bacteria that escape the phagosome into the cytoplasm.…”
Section: Discussionmentioning
confidence: 97%
“…However, a novel role for ubiquitin in regulating and facilitating bacterial killing is emerging. Burkholder et al showed that deubiquitinase inhibition significantly increases the translocation of inducible nitric oxide synthase (iNOS) to the phagosome and enhances the killing of Listeria monocytogenes [6]. Alonso et al .…”
Section: Introductionmentioning
confidence: 99%
“…In this experimental model the most significant DUB target of WP1130 has not been identified, but it induced killing of bacteria captured by phagosomes, likely by influencing iNOS localization to the phagosome [125]. Interestingly, WP1130 has been previously used in the treatment of malignancies, so it has been rather well characterized as a drug [123, 126, 127].…”
Section: The Perspectives For the Use Of Dubs In Antimicrobial Drumentioning
confidence: 99%